When the grass is always greener: practical equine weight management. (2nd March 2019) - Furtado, Tamzin; Perkins, Elizabeth; Pinchbeck, Gina; McGowan, Cathy; Watkins, Francine; Christley, Rob
Abstract : A research project byTamzin Furtado, Elizabeth Perkins, Gina Pinchbeck, Cathy McGowan, Francine Watkins and Rob Christley